Progressivism Leadership of Syaiful Hadi as Chancellor of IAIN Madura - Moh Elman; Fatimatuz Zahroh; Nur Izzatul Islam; Ryan Shobib (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2024)
Leadership is the natural potential of each individual which is developed through a process of firmly held values to achieve truth and goodness. The aim of this research is to determine the progress of Syaiful Hadi's leadership while he was Chancellor of IAIN Madura. This research describes 1) Syaiful Hadi's leadership as Chancellor of IAIN Madura in developing information technology (IT), 2) Syaiful Hadi's leadership as Chancellor of IAIN Madura in developing HR (Human Resources). The method in this research uses a qualitative approach with a case study type of research. The subject of this research is Syaiful Hadi as Chancellor of IAIN Madura. To achieve maximum results, researchers collected data through observation, interviews, and analysis of related documents. The results of this research can be concluded 1) Syaiful Hadi's leadership as Chancellor of IAIN Madura in the development of information technology (IT) has the ability to inspire his subordinates by creating a clear vision and motivating them to actively participate in achieving the goals that have been set, such as digitalization and increasing the capabilities of lecturers through the SLDP program, 2) Syaiful Hadi's leadership as Chancellor of IAIN Madura in HR (Human Resources) development is known for treating all campus residents regardless of their background. This shows that he values and cares about the needs and contributions of individuals on campus, creating an inclusive and supportive environment.